2020
DOI: 10.1002/jia2.25516
|View full text |Cite
|
Sign up to set email alerts
|

HIV prevalence, testing and treatment among men who have sex with men through engagement in virtual sexual networks in Kenya: a cross‐sectional bio‐behavioural study

Abstract: IntroductionIn Kenya, men who have sex with men (MSM) are increasingly using virtual sites, including web‐based apps, to meet sex partners. We examined HIV testing, HIV prevalence, awareness of HIV‐positive status and linkage to antiretroviral therapy (ART), for HIV‐positive MSM who solely met partners via physical sites (PMSM), compared with those who did so in virtual sites (either solely via virtual sites (VMSM), or via both virtual and physical sites (DMSM)).MethodsWe conducted a cross‐sectional bio‐behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 32 publications
2
27
1
Order By: Relevance
“…Studies have shown promising practices among the different approaches targeting men/male for improved HIV testing, prevention, treatment, care and support services. [43][44][45][46][47][48][49][50][51][52][53] Health facility-level factors We found significant variation in outcomes attributable to differences at the health facility level. The variations across facilities remained statistically significant, even after controlling for individual-level and facility-level factors (Models 2 and 3).…”
Section: Individual-level Factorsmentioning
confidence: 77%
“…Studies have shown promising practices among the different approaches targeting men/male for improved HIV testing, prevention, treatment, care and support services. [43][44][45][46][47][48][49][50][51][52][53] Health facility-level factors We found significant variation in outcomes attributable to differences at the health facility level. The variations across facilities remained statistically significant, even after controlling for individual-level and facility-level factors (Models 2 and 3).…”
Section: Individual-level Factorsmentioning
confidence: 77%
“…Missing this population from a HIV program would mean denying critical HIV prevention and treatment services to a very high risk and vulnerable sub-population of MSM. In Kenya, we previously found that MSM who operate through virtual sites alone had a much higher HIV prevalence (26.7%) compared to those who seek sexual partners in physical and virtual sites (15.4%) or only physical sites (8.5%) 14 . Identifying MSM who engage in these virtual sites provides an avenue to reach them with HIV prevention and care services.…”
Section: Discussionmentioning
confidence: 97%
“…Nearly three-quarters of the MSM mainly using virtual platforms also visited physical spots to find partners, which is in concurrence with another survey conducted among MSM in these three counties. The survey showed that 14.7% of the MSM sought male sexual partners only in physical sites, 64.0% in both physical and virtual sites and 21.2% in only virtual sites 14 . These findings warrant the importance of conducting mapping of both physical and virtual platforms, as developing size estimates from a single approach may underestimate the number of MSM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Kenya, key populations disproportionately contribute to the HIV epidemic and include female sex workers (FSW) and men who have sex with men (MSM), all of which experience disproportionately high prevalence of HIV at 29.3% and 18.9%, respectively (Bhattacharjee et al, 2020;Musyoki, Muraguri, Okal, & Kim, 2016;NASCOP, 2014). An estimated 18,000 PWID live in Kenya, primarily in Nairobi and coastal Kenya (NASCOP, 2019).…”
Section: Introductionmentioning
confidence: 99%